Penta Helix Element Synergy as an Effort to Develop Villages Tourism in Indonesia - Nurul Chamidah; Aditya Halim Perdana Kusuma Putra; Daduk Merdika Mansur; Budi Guntoro (Jurnal Manajemen Bisnis, 2021)
Objectively this study can be a critical review for the government or the stakeholders in the tourism industry to synergize with each other to realize the concept of Penta helix to be more productive and produce a conceptual model that can be empirically tested further. The research approach is to choose a qualitative explorative method that starts from the interview, discussion, and observation process involving informants representing each element of Penta helix. The study results indicate that Penta helix elements as stakeholders carry out activities and programs that consist of planning, implementation, and evaluation processes based on their respective capacities. Apart from that, the communication relationships between Penta helix elements have not shown an interactive and complicated relationship. The lack of communication is because of differences in perspective and the lack of coordination and collaboration between Penta helix parts. Exclusively the development of the Penta helix model is explained clearly in the discussion.